So much at stake: Ethical tradeoffs in accelerating SARSCoV-2 vaccine development. Issue 41 (22nd September 2020) - Grady, Christine; Shah, Seema; Miller, Franklin; Danis, Marion; Nicolini, Marie; Ochoa, Jorge; Taylor, Holly; Wendler, Dave; Rid, Annette
Highlights: Quickly finding a safe and effective vaccine against SARS Co-V-2 would be of great value. Collecting rigorous safety and efficacy data without compromising ethical and scientific norms is critical. The best approach is accelerated individually randomized controlled trials. Premature distribution could hamper public health and finding safe, effective SARS CoV-2 vaccines. Abstract: Background: A sense of urgency exists to develop vaccines against SARS CoV-2, responsible for numerous global cases and deaths, as well as widespread social and economic disruption. Multiple approaches have been proposed to speed up vaccine development, including accelerated randomized controlled trials (RCT), controlled human challenge trials (CHI), and wide distribution through an emergency use authorization after collecting initial data. There is a need to examine how best to accelerate vaccine development in the setting of a pandemic, without compromising ethical and scientific norms. Methods: Trade-offs in scientific and social value between generating reliable evidence about safety and efficacy while promoting rapid vaccine availability are examined along five ethically relevant dimensions: (1) confidence in and generalizability of data, (2) feasibility, (3) speed and cost, (4) participant risks, and (5) social risks. Results: Accelerated individually randomized RCTs permit expeditious evaluation of vaccine candidates using established methods, expertise, and infrastructure. RCTs are more likely than other approaches to be feasible, increase speed and reduce cost, and generate reliable data about safety and efficacy without significantly increasing risks to participants or undermining societal trust. Conclusion: Ethical analysis suggests that accelerated RCTs are the best approach to accelerating vaccine development in a pandemic, and more likely than other approaches to enhance social value without compromising ethics or science. RCTs can expeditiously collect rigorous data about vaccine safety and efficacy. Innovative and flexible designs and implementation strategies to respond to shifting incidence and test vaccine candidates in parallel or sequentially would add value, as will coordinated data sharing across vaccine trials. CHI studies may be an important complementary strategy when more is known. Widely disseminating a vaccine candidate without efficacy data will not serve the public health nor achieve the goal of identifying safe and effective SARS Co-V-2 vaccines.